1998
DOI: 10.1177/019394599802000106
|View full text |Cite
|
Sign up to set email alerts
|

The Decision to Lose Weight

Abstract: The purpose of this article is to describe the reasons people give for deciding to lose weight compared by weight history and gender. The sample consisted of 162 Caucasian community volunteers. Data were obtained from an extensive open-ended interview that was analyzed using content analysis. Respondents were categorized into five groups, according to their success at weight loss: Successful, Always Normal Weight, Underweight, Clinically Successful, and Always Obese. The Clinically Successful and Always Obese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 24 publications
1
45
1
Order By: Relevance
“…In line with our expectations, we found that perceived consequences of weight gain (adjusted for perceived weight, age and demographic co-variates) differed between men and women in the sample, with women perceiving greater negative health and appearance consequences it they were to gain weight. This was an anticipated finding, likely to reflect differences in weight consciousness between women and men [15,26,27,28]. Contrary to our hypothesis, there were no significant differences between the two age groups in terms of the extent to which they perceived negative health and appearance consequences although, among women, older participants reported fewer perceived consequences of weight gain for their appearance compared with younger women.…”
Section: Discussioncontrasting
confidence: 80%
“…In line with our expectations, we found that perceived consequences of weight gain (adjusted for perceived weight, age and demographic co-variates) differed between men and women in the sample, with women perceiving greater negative health and appearance consequences it they were to gain weight. This was an anticipated finding, likely to reflect differences in weight consciousness between women and men [15,26,27,28]. Contrary to our hypothesis, there were no significant differences between the two age groups in terms of the extent to which they perceived negative health and appearance consequences although, among women, older participants reported fewer perceived consequences of weight gain for their appearance compared with younger women.…”
Section: Discussioncontrasting
confidence: 80%
“…In our process of organising a comprehensive alternative to try to match gastric bypass, we found it necessary to learn more about patients' motivation for treatment. Recent research reveals an increased interest for obese patients' motivation with publications on topics including patients' expectations to and how patients value different treatment outcomes [6]; patients' reasons for wanting to loose weight [7][8][9]; and the possible link between motivation and treatment outcome [10]. However, literature provide only limited insight into why obese patients refuse treatment [3], and none at all on why they choose one treatment rather than another.…”
Section: Introductionmentioning
confidence: 99%
“…Medical events are commonly reported as triggers for weight loss initiation [1], but it is unknown whether experiencing a medical trigger is associated with better initial weight loss and sustained weight loss over time. In other areas of behavioral medicine, medical events have been shown to prompt long-term behavior change [2 -6].…”
Section: Introductionmentioning
confidence: 99%